2-Chloro-N-[4-(3-methyl-3-phenylcyclobutyl)-1,3-thiazol-2-yl]-N?-(naphthalen-1-ylmethylidene)acetohydrazide - Inkaya, Ersin; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Engin (Int Union Crystallography, 2011)
In the molecular structure of the title hydrazide derivative, C27H24ClN3OS, the acetohydrazide group is approximately planar, with a maximum deviation of 0.017 (3) angstrom. The dihedral angle between the naphthylene system and the phenyl ring is 78.91 (18)degrees. The crystal structure is stabilized by one weak intermolecular C-H center dot center dot center dot O hydrogen bond and two aliphatic C-H center dot center dot center dot pi hydrogen-bonding associations.